RANCANGAN PENGELOLAAN JURNAL ONLINE MAHASISWA MENGGUNAKAN OPEN JOURNAL SYSTEM (Studi Kasus : Prodi Teknik Informatika UIKA) - Fatimah, Fety; Jaenudin, Jejen (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2015)
In order to develop the onlinejournal of Informatics EngineeringDepartment into an online-basedscientific journal (e-journal) inInformatics Engineering. While thisresearch results of the students onlypublished without going through theprocess of learning, examination andediting. The purpose of the managementof online journals of students in order tomaintain the quality of journal researchresults and publications. In this study themanagement of student online journals(JOM) using Open Journal System (OJS).OJS is useful for managing its journalsfrom starting online submission, reviewerprocess, copyediting process,proofreading process, etc. until the scriptcan be published in OJS. All theseprocesses are done online using OJS. Thedesign of this JOM Management as amedium that can bridge the researchers(students) and reviewers (experts and thecampus) and to publicize the field ofinformatics engineering so that it can bedone effectively and efficiently.